The Activity Steps on the Life Process About the Post Disaster Sustainable Temporary Educational Buildings and Suggestions - Yusksel, Elif; Limoncu, Sevgul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
In addition to injuries and loss of life, natural disasters also damage the buildings and living spaces where people spend most of their time. Structural damage occurring after disasters interferes with housing, health, education and infrastructure. Education is one of the most important factors to consider. Education should not be interfered with during the temporary construction process. It is essential to build temporary educational facilities as quickly as possible in order to provide continuing education. Also, in order to reduce waste, it is essential that the temporary units provided are able to be used again for another disaster. The site, materials and structural system should be selected and applied properly. For this reason, the notion of sustainability should be considered throughout the entire process - site selection, design, production, construction, usage and post-usage processes of post-disaster educational buildings. In this study, the examination of the process of post-disaster sustainable temporary educational buildings will be carried out in order to establish post-disaster temporary educational building in accordance with sustainability criteria. This will allow students who are victims of disasters to continue their education and contribute the economy, while also protecting the country's natural resources.
Keywords: Disaster; sustainability; post-disaster sustainable temporary educational building; Architecture